From Intimacy to Currency: Self-Disclosure of Jak FM’s Sarapan Seru Radio Presenters as a Business Strategy - Rizky Kertanegara; Arius Krypton; Khairunnisa Devani Aqtus Permana Putri (Universitas Ahmad Dahlan, 2026)
Amid the dominance of digital media, radio faces sustained pressure to retain audiences and demonstrate business relevance. One distinctive asset is the on-air presenter’s capacity to build emotional closeness with listeners. This qualitative case study examines presenter self-disclosure as a communication strategy that converts into relationship currency for the industry. Data were gathered through in-depth interviews with two main presenters of the morning prime-time program Sarapan Seru on Jak FM Jakarta and analyzed thematically using a framework informed by Social Penetration, Parasocial Interaction, and Uses & Gratifications perspectives. Findings show that self-disclosure operates along two dimensions, breadth (topic variety) and depth (calibrated personal vulnerability), that jointly signal authenticity, catalyze parasocial companionship, and translate into observable participation (call-ins, direct messages/WhatsApp, voice notes, and other user-generated content). Building on these insights, the article proposes a conceptual pathway in which disclosure-driven intimacy functions as “relationship currency” that can be translated into sponsor-facing value propositions such as perceived brand-audience fit and the credibility of integrated host-read messages. The study contributes to radio and audio-media scholarship by linking relational communication mechanisms to media-economics logics, while acknowledging that commercial outcomes are inferred from qualitative insight rather than empirically measured.